Two-factor secure password manager - Jayakumar Sanjana (2017)
The usage of password managers nowadays has seen a tremendous increase. These applications provide many services to users that make user authentication easier. The password database is commonly locked by a master password, which when supplied allows the password manager to interact with the appropriate online services. This encrypted database is commonly stored entirely in a particular device, protected only by the master password. However, the exposure of the password could result in the disclosure of the entire database. The encrypted database still provides an opportunity to leak the passwords if decoded. This has brought about a need for improved security of these applications as they store critical information. The aim of this project is to reduce the risk of stolen encrypted database and master password by utilizing the Shamir’s secret sharing scheme that would split the database into many shares. This would implement a password storage that would store the split in multiple locations and utilize an authentication protocol that would require the exchange of these shares. A proof-of-concept to employ the splitting of storage and recombining of shared secrets to unlock the stored password is implemented. The possible security breaches that are applicable on the system are analyzed. Overall, through thorough investigation and experiments, the feasibility of the model is portrayed.